Efektivitas Penerapan Media Poster dalam Pembelajaran di Sekolah: Studi Literatur - Utami, Nuzula Laila; Lestari, Neta Dian; Aradea, Riswan (Yayasan Sembilan Pemuda Indonesia, 2024)
Posters are one of the excellent media for conveying information visually that is easy to understand. This study uses a descriptive literature study approach to analyze the application of poster media in learning, by collecting and reviewing relevant scientific articles. The results of the analysis show that posters are effective in improving the understanding of the material, especially through simplifying complex information into a simpler visual form to be understood. This study found that poster media has great potential to support learning success. However, its effectiveness is highly dependent on the quality of the poster design, the teacher's understanding in designing posters that are in accordance with learning objectives, and the visual characteristics of students. This study contributes that poster media has great potential to support learning success, but its success depends on design factors and the teacher's ability to integrate it into the learning process.